2021
DOI: 10.1159/000519933
|View full text |Cite
|
Sign up to set email alerts
|

Solid Pseudopapillary Neoplasm of the Pancreas: Unfolding an Intriguing Condition

Abstract: Pancreatic cancer is one of the most lethal malignant neoplasms, with a 1-year survival rate after diagnosis of 24%, and a 5-year survival rate of only 9%. While this illustrates the behavior of its main histologic type – ductal adenocarcinoma, there are other histologic subtypes of pancreatic cancer that can harbor excellent prognosis. Solid pseudopapillary neoplasm, described as a rare low-grade malignant neoplasm by the World Health Organization, is the best example of that, having an overall 5-year surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Confirming previous reports, we found that the majority of patients were female with a 9:1 ratio[ 12 ]. Other features, age, size, and tumor appearance were similar, with no statistical significance.…”
Section: Discussionsupporting
confidence: 92%
“…Confirming previous reports, we found that the majority of patients were female with a 9:1 ratio[ 12 ]. Other features, age, size, and tumor appearance were similar, with no statistical significance.…”
Section: Discussionsupporting
confidence: 92%
“…SPT frequently presents a single LMP neoplasm in the body and tail of the pancreas, which neither invades the surrounding structure nor causes biliary obstruction and metastasis, contributing to a 97% of an excellent 5-year OS rate. 17 All this may be a rationale for Dr. Shyr’s group to perform PHSS for SPT patients with/without ADP. 8 However, the literature review showed that recurrence or metastasis may occur after primary neoplasm resection, although it is a clinical situation of late recurrence, and it often occurs 8 to 16 years after surgery.…”
mentioning
confidence: 99%
“…8 However, the literature review showed that recurrence or metastasis may occur after primary neoplasm resection, although it is a clinical situation of late recurrence, and it often occurs 8 to 16 years after surgery. 17 Since the median follow-up period of Dr. Shyr's group was only 67.7 months (72.8 months in SPT patients without ADP and particularly short [25.8 months] in SPT patients with ADP), 8 it may be inappropriate to claim that this PHSS could be recommended for SPT patients with ADP to avoid pancreatic insufficiency by the authors.…”
mentioning
confidence: 99%
“…Solid pseudopapillary tumor of the pancreas is a particularly rare entity, usually affecting young women in their second and third decades of life, but cases have also been reported among pediatric patients [5]. Often imaging incidentalomas, these neoplasms are frequently located in the head or tail of the pancreas, but literature also mentions retroperitoneal, mesenteric or adrenal as possible locations [4]. The clinical picture is poor and nonspecific, in about only a third of cases associating abdominal pain and discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…[2] It is described in literature as having a low degree of malignancy, the metastases being exceptional. Surgery is curative in most cases [3,4].…”
Section: Introductionmentioning
confidence: 99%